Developing planning tools to overcome barriers to environmental behaviour - Gaytan Camarillo, Mariana (2023)
Responding to climate change has been challenging for everyone. While people express concerned about the environmental issue, yet they often fail to act on these concerns Research on pro-environmental behaviours and climate change has identified public perceptions and intentions as relevant determinants of behaviour, yet people do not always act on their intentions. This thesis aims to address the intention-behaviour gap between pro-environmental intentions and behaviour by examining the barriers to pro-environmental behaviours and using these to inform behavioural strategies using implementation intentions (Imps) to reduce the gap. The first study of this thesis explored the perceived barriers to pro-environmental behaviours, at the individual and collective level. Based on a classification of barriers by Gollwitzer and Sheeran (2006) a conceptual framework of barriers to goal completion was proposed. Findings indicated that, problems with remembering to act, and changing habits were highly prevalent within the barriers for individual pro-environmental behaviours. Whereas barriers related to differences of opinion and transferring guilt to others (e.g., others unwilling to change habits, favouring convenience) were the most common barriers to collective pro-environmental behaviours. Additionally, the classification of barriers indicated that for both individual and collective action, the main problems were related to the first engagement stage: getting started. The findings indicated that collective and individual behaviours face different barriers. The implications of the first study was the need for behavioural strategies to help people remember to engage with pro-environmental behaviours, one way to achieve this can be using planning tools such as implementation intentions (Imps). Thus, within this thesis three studies were developed (study two, three, and four) exploring the use of (Imps) to promote pro-environmental behaviours. Study two assess the use of visual imagery cues to make Imps memorable. Findings indicated that Imps had no impact on behaviour, but the presentation of images did make people reflect on whether pro-environmental behaviours could be part of their habitual life. Study three and four assessed the use of a new form of collective Imps, different from the one standardly assessed in the literature, to promote pro-environmental behaviours. In the experiments the Imps groups had if-then plans to help them engage with the goal-directed behaviours (e.g., If I encounter X, then I will do Y). Study three assessed the use of collective Imps (e.g., “If we notice our laptops are fully charged, then we will unplug them, and we will remind others to do the same”) to promote energy saving behaviours and study four used Imps formatted with shielding if-then action plans (e.g., “If I have leftovers, then I will try to eat them within the next two days and I will discuss my efforts with others”) to promote the reduction of food waste in households. Results indicated no effect of Imps on behaviour but showed behaviour changes over time in all experimental groups. For the literature on Imps, this implies that Imps may not effectively promote certain behaviours. Findings also indicate that the mere information about what behaviours can lead to the desired pro-environmental goal can impact behaviour change. For policymaking, results suggest that understanding people’s perceptions of barriers to sustainable behaviours are relevant for developing optimal policies. While Imps are not effective, just having people reflect on pro-environmental behaviour is effective in occasioning positive behaviour over time. Furthermore, encouraging habit-formation strategies that aim not only to start but also maintain engagement with pro-environmental behaviours could contribute to the battle against environmental issues.